2012
DOI: 10.1073/pnas.1119456109
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal biofilm-forming protein has a contiguous rod-like structure

Abstract: Staphylococcus aureus and Staphylococcus epidermidis form communities (called biofilms) on inserted medical devices, leading to infections that affect many millions of patients worldwide and cause substantial morbidity and mortality. As biofilms are resistant to antibiotics, device removal is often required to resolve the infection. Thus, there is a need for new therapeutic strategies and molecular data that might assist their development. Surface proteins S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 65 publications
(65 reference statements)
3
90
3
Order By: Relevance
“…1). We have previously shown that the E domain is fully unfolded in isolation (10). Because SasG domains have no tryptophans, (un)folding was followed by monitoring intrinsic tyrosine fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…1). We have previously shown that the E domain is fully unfolded in isolation (10). Because SasG domains have no tryptophans, (un)folding was followed by monitoring intrinsic tyrosine fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The length of the B region was shown to be critical for biofilm development because only SasG (or Aap) constructs with five or more B-repeats supported biofilm formation, while constructs with four or fewer B-repeats did not. Structural studies revealed that Aap B-repeats of the appropriate length adopt an elongated, rope-like structure coordinated by zinc ions and wrap around one another in an antiparallel fashion to form bundles of fibers that establish homophilic interactions and have the potential to interconnect neighbor cells (46,47).…”
Section: Fig 6 Effect Of Ph On the Isdc Expression And Biofilm Formatmentioning
confidence: 99%
“…The structural characterization of Aap and SasG in biofilm development has been recently defined (46,47). Aap and SasG comprise an N-terminal A region and repeated B domains toward the C terminus.…”
Section: Fig 6 Effect Of Ph On the Isdc Expression And Biofilm Formatmentioning
confidence: 99%
“…1). Several studies have demonstrated that Aap is a rod-like fibril extending from the cell surface (26,31,44). Bioinformatics analysis suggests Aap consists of two distinct domains, the A domain and B domain (28,45).…”
mentioning
confidence: 99%
“…Each of these B repeats is composed of 2 subdomains, G5 and E. The G5 unit is the functional component of the B repeat due to its propensity for self association; thus, it coordinates Aap-dependent intercellular interactions (27,30). E spacer regions are located between G5 units and likely prevent misfolding of the protein, a potential consequence of its extended fibrillar nature and repetitive domain architecture (44). Following extracellular export directed by the N-terminal signal sequence, Aap is anchored to the cell wall at the C-terminally located LPDTG sortase recognition motif (28,47).…”
mentioning
confidence: 99%